Plastic analysis-based seismic design method to control the weak storey behaviour of concentrically braced steel frames. (October 2016) - Merczel, D.B.; Aribert, J.-M.; Somja, H.; Hjiaj, M.
Abstract: This article focuses on the likelihood of the weak storey behaviour and the weak storey collapse of diagonally concentrically braced frames designed according to Eurocode 8 provisions. The emphasis is primarily put on the nature and development of the weak storey behaviour in order to designate the effects that shall be taken into account in an effective design procedure. In a second stage, the focus is on developing supplementary conditions to Eurocode 8 based on plastic analysis that can enhance the designs by preventing the occurrence of weak storeys. Highlights: Weak storey development of CBFs is an inherent property, not resistance issue. It is possible to capture instantaneous, inelastic, seismic CBF response characteristics with imperfect elastic models. Interrelation of cumulating plastic deformation and degradation of braces, change of response characteristics, localisation of drifts, and the development of the weak storey behaviour Description of the weak storey development as a gradual, self-amplifying recurring loop Identification of insufficiencies in the Eurocode 8 design procedure of CBFs: uniformity condition, participation of columns, local brace slenderness.